Multiple role stress, burnout, and job satisfaction of female sales promos - Cunanan, Stephany May M.
This is a descriptive study aimed to determine the multiple role stress, burnout, and job satisfaction of selected female sales promos from a certain mall. It was found out that both single and married female sales promos experienced moderate level of stress in combining work and family roles. However, their primary sources of stress differed from each other. Their activities spent at home also varied due to their different roles. Both groups also experienced moderate level of burnout which is caused mostly by being physically exhausted with their jobs. Despite the experience of stress and burnout, they reported high satisfaction towards their jobs.